The draining of the Fens projectors, popular politics, and state building in early modern England - Ash, Eric H., 1972- (Johns Hopkins studies in the history of technology, 2017)
"This book is a political, social, and environmental history of the many attempts to drain the Fens of eastern England during the late sixteenth and seventeenth centuries, both the early failures and the eventual successes. Fen drainage projects were supposed to transform hundreds of thousands of acres of wetlands into dry farmland capable of growing grain and other crops, and also reform the sickly, backward fenland inhabitants into civilized, healthy farmers, to the benefit of the entire commonwealth. Fenlanders, however, viewed the drainage as a grave threat to their local landscape, economy, and way of life. At issue were two different understandings of the Fens, what they were and ought to be; the power to define the Fens in the present was the power to determine their future destiny. The drainage projects, and the many conflicts they incited, illustrate the ways in which politics, economics, and ecological thought intersected at a time when attitudes toward both the natural environment and the commonwealth were shifting. Promoted by the crown, endorsed by agricultural improvement advocates, undertaken by English and Dutch projectors, and opposed by fenland commoners, the drainage of the Fens provides a fascinating locus to study the process of state building in early modern England, and the violent popular resistance it sometimes provoked. In exploring the many challenges the English faced in re-conceiving and re-creating their Fens, this book addresses important themes of environmental, political, economic, social, and technological history, and reveals new dimensions of the evolution of early modern England into a modern, unitary, capitalist state"--